An operating simulation tool for modelling and managing a job shop system. (24th April 2019) - Bottani, Eleonora; Rinaldi, Marta; Montanari, Roberto; Bertolini, Massimo; Zammori, Francesco
This study analyses the machinery department of a major Italian company, which manufacturers' equipment and plants for the food industry. At present, the machinery department is arranged as a pure job shop and the firm adopts a push strategy: every week the accepted orders are released in the shop floor and sequenced accordingly to the earliest due date dispatching rule, with no pre-emption. Yet, the resulting performance is not satisfactory: often the jobs are not completed within the planned week and work in progress accumulates in the shop floor increasing time and costs. Aiming to improve the current situation, especially in terms of makespan minimisation, the system has been first reproduced using the simulation environment SIMUL8™ and then different dispatching rules have been tested through simulation. Finally, the simulation model was turned into an operating tool that may support the production manager in selecting the most favourable dispatching rule depending on the list of jobs to be processed and on the current system's state. This tool was tested using historical data on the machinery department; the results obtained demonstrated the superiority and robustness of the proposed approach.